Impactos de eventos chuvosos na dinâmica físico-química e biológica em reservatórios urbanos estudo de caso: Lagoa da Pampulha - Julio Cesar Borges Belico (2017)
The Lagoa da Pampulha (Belo Horizonte, Brazil) is a shallow hypereutrophic urban reservoir, which shows in the last years continuous dominance of cyanobacteria. Researches in tropical ecosystems point to a strong relationship between the rain seasonality and the phytoplankton biomass and composition, mainly in eutrophic ecosystems. This study investigates the dynamic of a tropical reservoir in relation to rain episodes through analyses of monthly samples and high frequency monitoring (2011-2015), coupled with the application of an ecohydrodynamic model GLM-AED. The model validation obtained a satisfactory annual RMSE of 1,01 °C for the thermal profile and 72,31 µg. Chl.l-1 for the superficial phytoplankton biomass, in a year witch the laboratory measured values ranged between 120,23 and 442,44 µg. Chl-a.l-1 . It was evidenced that the immediate effects of rainfall events are the reservoir conductivity and phytoplankton biomass decrease, with its occurrence linked to the raise in water transparency. The continuous surface temperature measurements made by the probe and the GLM-AED simulations showed that the influence of rainfall on the epilimnion temperatures are very low, and its variations are mostly due to air temperature and incoming shortwave radiation changes in the precipitation events. Indeed, the events duration and total precipitation were the events characteristics better correlated with variations in the reservoir parameters measured by the probe and simulated in the model. In summer, the thermal stratification is very strong, and rainfall events were usually not capable of breaking it, leading to a decrease in the hipolímnion temperatures and a reduction of the mixing zone. When the cold and dry season arrives, the reservoir is more susceptible to destratification, and this phenomenon occurrence was noted in April to May in all years during the study period, accompanied or not by rainfall events. In this season the wind appears to play an important role in the reservoir, promoting the reservoir mix and incorporating autochthones nutrients in the surface, been noted a distinguish temporal and spatial distribution on its occurrence